2019
DOI: 10.1111/bjet.12787
|View full text |Cite
|
Sign up to set email alerts
|

Look who’s talking: Exploring instructors’ contributions to Massive Open Online Courses

Abstract: Previous research on xMOOC pedagogy has established that learner interactions in discussion forums play a fundamental role in learning. However, little is known about the extent to which MOOC instructors engage with learner conversations and the impact this has on learner engagement. Adopting a novel design, this study went beyond self-reported methods, and combined transcript analysis and in-depth interviews to examine the dynamics of learner-instructor interactions and to revisit the use of the Community of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
10
0
2
Order By: Relevance
“…Although previous studies have reported that the use of vocatives was often found in teachers' facilitation in online asynchronous discussions and MOOC education (e.g. Evans et al, 2020; Goshtasbpour et al, 2020), research has also reported that online students used a lot of vocatives via online communication tools like Twitter (e.g. Baisley‐Nodine et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have reported that the use of vocatives was often found in teachers' facilitation in online asynchronous discussions and MOOC education (e.g. Evans et al, 2020; Goshtasbpour et al, 2020), research has also reported that online students used a lot of vocatives via online communication tools like Twitter (e.g. Baisley‐Nodine et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Development of online learning infrastructure created alternative learning environment for the students and to avoid disrupted education system (Kumar, 2019). Almost all the institutions have established online systems so that course contents could be deliver online and may engage students and conduct assessments in better way (Goshtasbpour et al, 2020;Safdar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Summarising discussions and bringing them together at different points during a course are essential for building and communicating a shared understanding (Garrison 2017). Our study (Goshtasbpour et al 2020) shows that this occurs only rarely in large courses, and as a result, learners may not be provided with enough opportunities to recognise their misconceptions and confirm a shared understanding. Therefore, ensure that either you, or a learner, summarise the discussion.…”
Section: Provide Explicit Academic Leadershipmentioning
confidence: 72%
“…In most cases, an educator's comment tends to end the discussion and reduce the opportunities for turn-taking and collaborative activities (Goshtasbpour et al 2020). Sometimes this is because learners have received the validation or information they sought from an educator, but it can also be due to the educator's move, i.e.…”
Section: Ensure Continuity Of Discussion When You Contributementioning
confidence: 99%
See 1 more Smart Citation